Metalanguage from abstract to concrete from simple to complex - Rodríguez Orellana, Mauricio Alberto (Editorial no identificada, 2024)
Humans try to communicate, that is one truth of what it means to be human. As a human being you generate an idea and communicate to others. It could have started when a caveman tried to say to another that he needed help to move a big rock. The same way administration and teamwork could have begun. After some time and based on region languages began to pop up, like daisies, on the regions humans were living (this goes from all the regions that have live or dead languages) based on the civilizations that do work with them. What can be interesting to work on is that all the languages ended up having the same pieces but with different execution. This means every language has the Parts Of Speech and works them in different ways.